Special interest tourists collecting places and destinations: A case study of Australian World Heritage sites - King, Lisa M.; Prideaux, Bruce (Journal of vacation marketing, 2010)
The World Heritage brand signals the best in protected areas. Certain destinations and places hold particular appeal to special interest tourists resulting in the conscious collection of those sites. TV programs, authors and others take advantage of this penchant to collect places; yet, there is little literature on this behaviour. This paper reports on research testing the contention there is a specific group of visitors who collect World Heritage listed sites. The article examines World Heritage visitor recognition prior to and after time on-site. A case study approach is applied and visitor surveys used across five Australian properties. Findings demonstrate only 13% of site visitor do collect World Heritage Areas but their socio-demographics profiles are too diverse to develop a specific socio-demographic profile of this group. Additionally, only 60% of respondents knew they were visiting a World Heritage listed site indicating a significant weakness in the World Heritage brand.